Odpowiedź :
Odpowiedź:
[tex](1+sin\alpha )(\frac{1}{cos\alpha } -\frac{sin\alpha }{cos\alpha }) =(1+sin\alpha ) \cdot \frac{1-sin\alpha }{cos\alpha } =\frac{1-sin\alpha }{cos\alpha } +\frac{sin\alpha (1-sin\alpha )}{cos\alpha } =\frac{1-sin\alpha +sin\alpha -sin^2\alpha }{cos\alpha }=[/tex]
[tex]=\frac{1-sin^2\alpha }{cos\alpha } =\frac{cos^2\alpha }{cos\alpha } =cos\alpha[/tex]
Odpowiedź:
Szczegółowe wyjaśnienie:
c)
(1+sin α ) razy { (1/cos α) - (sin α/ cos α) } = (1+sin α) razy { (1-sin α) / (cos α)} = { (1+sin α) razy (1-sin α) } / cos α) = (1 -sin² α) / cos α = cos² α / cos a
= cos a